Factors Affecting Employee Performance in Manufacturing Companies: Empirical Studies in Batam City - Siagian, Chelika; Dr. Muhammad Donal Mon (Universitas Airlangga, 2024)
Background: The progress of a company is greatly influenced on the performance of its employees working in the company. In this case, the performance of each employee is influenced by several factors. Self-efficacy, organizational support, and good management skill are the aspects which define employee performance's quality. Objective: The current field study conducted by staffing researchers in Batam City, shows that employee performance is a very important aspect for increasing productivity and business progress. Employees who can demonstrate knowledge, technical skills, creativity, and organizational experience are very important since they are seen as productive assets which can improve company's performance as well as company's reputation. Method: This study was conducted on 270 employees in manufacturing companies in Panbil Area, Batam, Indonesia. This study used Smart PLS 3.0 with multiple linear regression to examine the factors that affect employee performance. Results: This study found that the results of motivation; transformational leadership; organizational culture; work discipline; job performance; and employee performance have a significant influence on employee performance. The five independent variables have a significant effect on employee performance simultaneously. Conclusion: Based on the results of this research study, the researcher found that every company will always develop employee performance to achieve company goals. Human resource management needs to apply effective leadership and in accordance with the circumstances in the company. Not only leadership, work environment conditions and motivation, suitable job description will affect employee performance. Working environment conditions that can motivate employees to work will certainly develop employee performance. Keywords: motivation; transformational leadership; organizational culture; work discipline; job performance; employee performance